Modeling of Column Apparatus Processes - Boyadjiev, Christo; Doichinova, Maria; Boyadjiev, Boyan; Popova-Krumova, Petya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This new edition includes brand-new developments in the modeling of processes in the column apparatuses. It analyzes the radial velocity component and axial variation in the axial velocity in the column. These models are described in five new chapters. The book presents models of chemical and interphase mass transfer processes in industrial column apparatuses, using convection-diffusion and average-concentration models. It also introduces average concentration models for quantitative analysis, which use the average values of the velocity and concentration over the cross-sectional area of the column. The new models are used to analyze a broad range of processes (simple and complex chemical reactions, physical and chemical absorption, physical and chemical adsorption, catalytic reactions in the cases of physical and chemical adsorption mechanism), and make it possible to model sulfur dioxide gas purification processes.
Introduction -- Part I: Qualitative Analysis of Column Apparatuses Processes -- One-Phase Processes -- Two-Phase Processes -- Three-Phase Processes -- Part II: Quantitative Analysis of Column Apparatuses Processes -- Column Reactors Modeling -- Interphase Mass Transfer Processes Modeling -- Industrial Column Chemical Reactors -- Part III: Computer Calculation Problems -- Perturbation Method Approach -- Two-Coordinate Systems Problem -- Multi-Step Modeling Algorithms -- Part IV: Waste Gases Purification in Column Apparatuses -- Bi-Zonal Absorption Apparatus -- Absorption-Adsorption Method -- Co-Current Apparatus -- Part IV: Modeling of Processes in Industrial Column Apparatuses. Industrial Types of Convection-Diffusion and Average-Concentration Models.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Chemistry, Technical; Continuum mechanics; Fluid mechanics; Engineering Thermodynamics, Heat and Mass Transfer; Industrial Chemistry; Continuum Mechanics; Engineering Fluid Dynamics